Preliminary experience with MEDGAL DHS for treatment of proximal femoral fractures - Oldani, Danila; Maniscalco, Pietro (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the study: The Authors report their implant’s analysis and preliminary experience with a new fixation device, the MEDGAL DHS for treatment of proximal femoral fractures, producted by MEDGAL Sp.z o.o, Niewodnicka, Poland. Materials: Between January 2019 and September 2019 in Orthopedics and Traumatology Department of Piacenza, 12 patients with stable pertrocanteric fractures were treated with the MEDGAL DHS. Results: No patients presented perioperative complications with low bleeding and mean surgical time of 40 minutes. Conclusions: DHS is an optimal implant for the treatment of stable pertrochanteric femural fractures.